The effect of various atmospheres on the threshold fatigue crack growth behavior of AISI 304 stainless steel - Kelestemur, MH; Chaki, TK (Elsevier Sci Ltd, 2001)
The threshold fatigue crack growth (FCG) behavior of AISI 304 austenitic stainless steel was investigated under three different atmospheres: dry argon, hydrogen and moist air. FCG tests were performed with an MTS 810 servohydroulic machine on compact tension specimens and crack closure measurements were done with an extensometer. A Plexiglass environmental chamber was built to control the atmosphere. Ferrofluid tests were applied to determine the transformed martensitic structure. The results of tests done under the three different atmospheres showed that the material is sensitive to the hydrogen atmosphere. Partial intergranular and transgranular fracture was observed at the fracture surface of the material tested under argon. However, the nature of the fracture was only transgranular under both hydrogen and moist air. Hydrogen degradation was attributed to hydrogen embrittlement and the material did not show threshold behavior at the near-threshold region. Comparison of results obtained in argon and moist air showed that the latter slightly influenced the crack growth rate. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: fatigue crack growth; threshold; stainless steel; hydrogen embrittlement